Methane seepage activities in the Qiongdongnan Basin since MIS2 - Luo, Xiaokang; Yuan, Yajuan; Zhang, Wei; Huang, Wei; Ou, Shimin; Ji, Chunsheng; Cao, Jun (Frontiers in Marine Science, 2024)
Gas hydrates are globally acknowledged as a significant strategic alternative energy source, and there is a consensus on the necessity to enhance their exploration. However, gas hydrates are highly prone to decomposition under variations in external environmental conditions, which can result in subsea methane seepage activities. Consequently, investigating subsea methane seepage activities holds substantial theoretical and practical significance for exploring gas hydrates. This paper evaluates the history of methane seepage activities in the Qiongdongnan Basin (QDNB) by analyzing the carbon and oxygen isotopic characteristics of benthic foraminifera and the geochemical properties of pore water from gravity sediment cores at sites QH-CL4 and QH-CL40. The results indicate that since the Marine isotope stage2 (MIS2), continuous micro-methane seepage activity has been present in the Qiongdongnan Basin, characterized by a slight negative deviation in the carbon isotopes of benthic foraminifera. Methane seepage activity intensified during 14.6 ka BP and between 19.64-23.22 ka BP. This increase is thought to be associated with rising seawater temperature during the Allerød interstadial and declining sea level during the Last Glacial Maximum, respectively. Moreover, current geochemical characteristics of pore water reveal strong methane seepage activity, with flux as high as 28.968 mmol•m⁻²•a⁻¹. This ongoing activity has led to gas hydrate formation within shallow layers while also causing negative deviations in pore water salinity.